Prediction of the Impact of CYP2C19 Polymorphism on Drug-Drug Interaction between Voriconazole and Tacrolimus Using Physiologically-Based Pharmacokinetic Modelling - Zhi-Ping Jin; Miao Yan; Si-Ze Li; Bao-Qing Wang; Qing Xu; Wei Wu; Xiao-Yu Li; Qian-Zhou Lv; Xiao-Qiang Xiang (Universidade de São Paulo, 2023)
Abstract Voriconazole increases tacrolimus blood concentration significantly when coadministrated. The recommendation of reducing tacrolimus to 1/3 in voriconazole package insert seems not to be satisfactory in clinical practice. In vitro studies demonstrated that the magnitude of inhibition depends on the concentration of voriconazole, while voriconazole exposure is determined by the genotype status of CYP2C19. CYP2C19 gene polymorphism challenges the management of drug-drug interactions(DDIs) between voriconazole and tacrolimus. This work aimed to predict the impact of CYP2C19 polymorphism on the DDIs by using physiologically based pharmacokinetics (PBPK) models. The precision of the developed voriconazole and tacrolimus models was reasonable by evaluating the pharmacokinetic parameters fold error, such as AUC0-24, Cmax and tmax. Voriconazole increased tacrolimus concentration immediately in all population. The simulated duration of DDIs disappearance after voriconazole withdrawal were 146h, 90h and 66h in poor metabolizers (PMs), intermediate metabolizers (IMs) and extensive metabolizers(EMs), respectively. The developed and optimized PBPK models in this study can be applied to assit the dose adjustment for tacrolimus with and without voriconazole.